Optimal Solar Cable Selection For Grid-Connected Photovoltaic Systems - Mosheer, Ahmed Daud (2016)
As a solution for the depletion of fossil fuel and its influence on the environment (i.e. CO2), photovoltaic (PV) systems have been considered as alternative renewable energy (RE) resources. The common practice in sizing the solar cables of photovoltaic systems follows the maximum voltage drop and thermal limit constraints (i.e. maximum allowed current and maximum allowed voltage drop). Little attention has been paid on the estimation of the annual energy losses for solar cables. According to Malaysian standards, for solar cable sizing, the maximum allowed voltage drop is five percent. Though seemingly insignificant, a five percent voltage drop losses, when calculated throughout the life span of a photovoltaic system, will have a huge impact on the profitability of the PV system. This dissertation presents investigation on the annual energy losses for standard solar cables. More importantly, instead of using conventional methods that follows the maximum allowed voltage drop and maximum allowed current calculations for sizing the solar cables, this dissertation presents a method for selecting optimal solar cable capacity for grid-connected solar Photovoltaic (PV) systems. The optimization method takes into consideration the cost of losses and solar cable investment cost throughout the technical lifespan of the cable. In addition, the effects of using actual field data of different time resolution irradiation data on the calculation of energy losses, and optimal solar cable selection are presented and discussed in this dissertation. Additionally, the sensitivity of different feed-in tariff rates on optimal solar cable selection had been considered in this work. The key findings of the dissertation suggest that oversizing the solar cable for PV system plays an important role in losses reduction, and at the same time yields monetary savings in the long run. Also, the results showed that the time resolution solar radiation data has important role on optimal solar cable selection and economic calculations of PV system.